2006
DOI: 10.1080/01490400600598053
|View full text |Cite
|
Sign up to set email alerts
|

Boredom in Free Time: Relationships with Personality, Affect, and Motivation for Different Gender, Racial and Ethnic Student Groups

Abstract: The propensity to experience boredom in free time was investigated by exploring relationships with the individual's demographic characteristics, personality, motivational orientation, and affective style assessed through group-administered questionnaires to 999 university students. The self-as-entertainment personality attribute consistently predicted the likelihood that students would be bored, and inverse relationships with extraversion and intrinsic motivational orientation were found for all student groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 79 publications
2
44
0
3
Order By: Relevance
“…Females in South Africa (Wegner et al 2006) and in rural areas of Australia (Patterson et al 2000) experienced higher levels of boredom than boys. Gender significantly moderated relationships between individual characteristics and boredom in free time (Barnett and Klitzing 2006). Other studies found that males reported higher boredom (Shaw et al 1996) and were more prone to boredom (Newberry and Duncan 2001) than females.…”
Section: Gender and Identitymentioning
confidence: 80%
See 3 more Smart Citations
“…Females in South Africa (Wegner et al 2006) and in rural areas of Australia (Patterson et al 2000) experienced higher levels of boredom than boys. Gender significantly moderated relationships between individual characteristics and boredom in free time (Barnett and Klitzing 2006). Other studies found that males reported higher boredom (Shaw et al 1996) and were more prone to boredom (Newberry and Duncan 2001) than females.…”
Section: Gender and Identitymentioning
confidence: 80%
“…A description of the study samples, measurements and variables is given in Appendix 1. The majority of the studies were conducted in the developed world, with 16 studies from the USA (Barnett 2005, Barnett and Klitzing 2006, Caldwell et al 1999, Caldwell and Kivel 1998, Caldwell and Smith 1995, Iso-Ahola and Crowley 1991, Iso-Ahola and Weissinger 1990, Larson and Richards 1991, Newberry and Duncan 2001, Sharp et al 2006, Weissinger, Caldwell and Bandolas 1992, Widmer, Ellis and Munson 2003, Widmer, Ellis and Trunnell 1996, Yang and Yoh 2005. Two studies were from Canada Weissinger 1992, Shaw, Caldwell andKleiber 1996) and three studies were from Australia (Farnworth 1998, Gordon and Caltabiano 1996, Patterson, Pegg and Dobson-Patterson 2000.…”
Section: Study Locationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kinnaird (1994), Annett et al (1995), Thapa et al (2004), Papadakis et al (2004), Johnson et al (2001), Barnett and Klitzing (2006) and Todd et al (2001) stated in their studies that gender has an effect on motivation. The users of Goksu Park are mostly male.…”
Section: Discussionmentioning
confidence: 99%